Post-wrinkling behavior of webs in GFRP cell-core sandwich structures. (15th March 2016) - Manshadi, Behzad D.; Vassilopoulos, Anastasios P.; Keller, Thomas
Abstract: Similarly to the post-buckling behavior of steel girder webs, the post-wrinkling behavior of glass fiber-reinforced polymer (GFRP) cell-core sandwich webs can increase their ultimate shear strength. Post-wrinkling is, however, different from post-buckling since wrinkling is a local buckling instability mode that can occur in any part of the web. Furthermore, all the previously presented theories or models have been limited to isotropic web plates, while the fiber architecture of orthotropic plates can greatly influence post-wrinkling behavior. Based on biaxial compression–tension experiments on GFRP web-core sandwich panels, the redistribution of the strain field during post-wrinkling was examined for two different fiber architectures, [90/0] and [±45] stacking sequences. The results proved that fiber architecture greatly influences the wrinkling loads and wrinkling mode as well as post-wrinkling behavior. During post-wrinkling, the ultimate shear strength of the sandwich structure and the redundancy of the system can be increased, thus enhancing the safety, functionality and reliability level of this type of structure.